2015
DOI: 10.1521/jscp.2015.34.6.508
|View full text |Cite
|
Sign up to set email alerts
|

Does Alcohol Reduce Social Anxiety in Daily Life? A 22-Day Experience Sampling Study

Abstract: To explain the co-occurrence of social anxiety and alcohol use problems, researchers have used experimental methods to test whether alcohol reduces state social anxiety (SSa) in the lab. The present study used experience sampling to extend research into real world settings. Students (N = 132; 100 women; 32 men; aged 17 to 32 years) reported their SSa and alcohol intake 6 times from 4:00 pm to 4:00 am every day for 22 days. multilevel modeling suggested for each alcoholic drink consumed, SSa decreased by 4.0% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 54 publications
1
10
0
7
Order By: Relevance
“…No outliers were detected using our pre-registered methods of examining extreme values in the distribution (Z > 3.30) or effect sizes with confidence intervals (CIs) which did not overlap any other individual CIs or the pooled estimate. Four cases were identified by Cook's Distance to be influential [30,[55][56][57], therefore we analysed all data with these data points included and excluded. Data are reported with the data points included unless exclusion significantly influenced the results.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…No outliers were detected using our pre-registered methods of examining extreme values in the distribution (Z > 3.30) or effect sizes with confidence intervals (CIs) which did not overlap any other individual CIs or the pooled estimate. Four cases were identified by Cook's Distance to be influential [30,[55][56][57], therefore we analysed all data with these data points included and excluded. Data are reported with the data points included unless exclusion significantly influenced the results.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Furthermore, numerous studies have examined compliance as a function of total assessment period (i.e. duration of study), and demonstrated that compliance declines as the study progresses [29][30][31]. However, others have failed to replicate these observations [7] [32].…”
Section: Introductionmentioning
confidence: 99%
“…Psychiatric disorders and SUD commonly co-occur and frequently have a complex bidirectional relationship such that substance use can exacerbate symptoms related to psychiatric disorders while psychiatric disorders may conversely trigger substance use (Mueser, Drake, & Wallach, 1998). For example, symptoms of social anxiety may trigger drinking alcohol due to its ability to reduce uncomfortable feelings (Battista et al, 2015). Unfortunately, psychiatric comorbidity within SUD is frequently associated with greater impairment and poor treatment engagement (Greenfield et al, 1998; Weinstock, Alessi, & Petry, 2007), both of which can lead to poor treatment outcome and relapse to substance use.…”
Section: 2 Rationale For Exercisementioning
confidence: 99%
“…In one recent study on the effect of alcohol on social anxiety in real world settings amongst non-clinically anxious people, daily experience sampling revealed that subjective social anxiety was reduced on average by 4% with every alcoholic drink consumed (Battista et al, 2015). Additionally, a number of individual difference variables such as coping style, impulsivity, and alcohol use expectancies likely influence the relationship between social anxiety and alcohol use (Battista et al, 2010; Cooper et al, 1992; Morris et al, 2005; Nicholls et al, 2014).…”
Section: The End-directed Use Of Alcoholmentioning
confidence: 99%
“…Thus, affective homeostasis usually results from the perceived successful management or perceived absence of social threats. However, it may also result from the ingestion of particular psychoactive compounds like alcohol, which can artificially down-regulate negative affective states (Battista et al, 2015). In essence, alcohol has the capacity to subdue unpleasant subjective anxiety, thereby artificially signaling that an antecedent threat has been managed successfully, or that there are no pressing social threats.…”
Section: The Artificial Management Of Social Threatsmentioning
confidence: 99%